Microsatellite marker characterization of Chilean Common Bean (Phaseolus vulgaris L.) germplasm - Becerra Velásquez, Viviana L.; Paredes, M; Rojo, C; Díaz, Lucy Milena; Blair, Matthew W. (Wiley, 2010)
The Chilean national common bean germplasm collection consists of 1200 accessions, most of which have not been characterized or used in breeding programs. As part of the characterization of this germplasm we have formed a core collection of 246 accessions that represent 21% of the whole collection and that consists of many race Chile representatives as well as varieties from other races that are traditionally grown in the country. The specific objectives of this work were to use microsatellites to evaluate the level of polymorphism in the Chilean core collection and to determine the genetic variability of race Chile and its relationships with other races. The results indicate that the level of polymorphism detected with microsatellites was higher than that obtained with previous molecular or biochemical markers. The number of microsatellite alleles varied from 2 to 14 and the polymorphism information content (PIC) values were 0.08 to 0.84. Heterozygosity ranged from 0 to 0.052 for each of the markers. Euclidean genetic distance ranged from 0.12% between race Chile and race Nueva Granada to 0.71% between race Chile and race Mesoamerica. Multiple correspondence analysis (MCA) showed clustering of the accessions into the two main genepools, with race Chile genotypes grouping mainly with race Nueva Granada genotypes.